CRAbCVE- Uma arquitetura para viabilização de CVEs através da Internet - Gomes, George Allan Menezes (2005)
Although the complexities of many tasks encountered in modern societies require the join effort of groups of people in order to be accomplished, cooperative work is still a difficult job. Usually the difficulties arise due to lack of appropriate coordination, poor definition of the context in which the activities are to be performed individually or in group; thus, generating redundancies, inconsistencies and contradictions within the workgroup. In order to overcome these problems, a new field of research, called Computer Supported Cooperative Work (CSCW), was created to seek means of properly supporting work groups. Despite the favorable results achieved by CSCW, thus far, tools that provide a high level of interaction among the group members and the leaders of sub-groups are still not satisfactory. The use of virtual reality within cooperative systems allows the interactions among participants to be highly spontaneous, because, in virtual environments, communication by means of image, text and audio is possible. The Collaborative Virtual Environments (CVEs), which employ shared virtual reality technology, have proved to possess great potential for collaborative work. Therefore, collaborative virtual environments have been developed taking into consideration the results obtained by CSCW research. Nonetheless, developing CVEs is complicated, since they demand a great deal of resources, and need to incorporate concepts and recommendations from several research fields, such as Virtual Reality (VR), Computer Supported Cooperative Work and l Distributed Computing. The main objective of this dissertation is to design a generic architecture (CRAbCVE) for allowing distribution of several collaborative virtual environments within a network of servers on the Internet. This architecture defines specialized components, capable of distributing the processing that takes place in the CVE, thus obtaining a great computational power at low costs. Another important objective is the specification of a Model of Authorship in CVEs (MAC) for helping to integrate the CRAbCVE architecture into the framework of collaborative work. All models proposed herein have been incorporated into a prototype system and a simple case study has been analyzed.